The effects of glibenclamide on thyroid function tests in type 2 diabetic patients - Marwan M. Merkhan (University of Mosul, 2013)
Objective: to determine the long-term effect of glibenclamide on thyroid function tests in type 2 diabetic patients. Materials and methods: A total of 63 diabetic patients, 32 type 2 on glibenclamide and 31 type 1 on insulin, were enrolled in this study. Thirty two, apparently healthy volunteers, were also included in the study as a control group. Blood samples were taken from the patients and controls, then the serum were analysed for measurement of fasting serum glucose (FSG), thyroid hormones (total T3, fT3, total T4, fT4) and TSH. Results: the result showed that there were no significant differences between thyroid hormones and TSH of the glibenclamide group when compared to the same parameters in the control group, however the fT3 and fT4 of insulin group were significantly lower than that of the control and glibenclamide groups. There were no significant differences between total T3 and total T4 of control, glibenclamide and insulin groups when compared to each others, whereas the TSH of insulin group was significantly higher than that of control and glibenclamide groups. Conclusion: long term therapy with glibenclamide have no effect on thyroid function tests in type 2 diabetic patients and there was no correlation between glycemic control and thyroid hormones or TSH.